(untitled) (CAHIERS MAGELLANES-NS, 2024)
This paper examines the various schemes implemented by the Government of India aimed at alleviating poverty and improving the socio-economic conditions of the underprivileged sections of society. Poverty alleviation has been a central theme in India's development agenda, with numerous programs and policies designed to provide financial support, improve access to education and healthcare, and enhance livelihoods. This study analyzes the impact of major schemes such as the Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA), Pradhan Mantri Awas Yojana (PMAY), National Rural Livelihoods Mission (NRLM), and other flagship initiatives. The effectiveness of these schemes in reducing poverty and their challenges are discussed, providing insights into potential improvements and future directions for policy makers.